Review of collective teacher efficacy research: Implications for teacher development, school administrators and education researchers - Visal Moosa (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
Out of around two hundred different variables that are known to have some relation with student achievement, Collective Teacher Efficacy (CTE) was reported to be among the most influential. Hence, CTE has received attention of many researchers as a topic investigation. The purpose of the present review is two-fold; (a) to present an overview of research on CTE, and (b) to draw some implications and suggest some recommendations for teacher development, school administration and further research on the topic. This paper engaged the methodology of systematic literature review to collect data from Google Scholar database.Ã‚Â Sixty-six sources were employed in the review. During the analysis, the reviewed papers were sorted into categories and themes based on their major focus. The results revealed four major factors that influence CTE; (i) principleÃ¢â‚¬â„¢s leadership, (ii) teacher professional learning, (iii) teachersÃ¢â‚¬â„¢ self-efficacy, and (iv) organisational factors. Furthermore, it was also found that CTE has a significant impact on (i) student learning, and (ii) teacher learning. The findings imply that (i) teacher development should providing avenues to improve teacher efficacy, (ii) school administrators need to focus on what might enhance teacher learning in school in order to foster positive CTE beliefs, and (ii) further research is needed in investigating the indirect link CTE has with leadership and relational/structural conditions in schools. Learning process as essential components of distance learning (synchronous or asynchronous).